Maastrichtse industriëlen en het Belgische annexisme in de jaren 1918–1919 - Beaumont, Eddy de (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2023)
Abstract: „During and immediately after the First World War the Belgian government developed plans to annex parts of the Netherlands after the war, such as the province of Limburg. How did industrialists in the capital Maastricht respond to these Belgium goals? In this article, I explore the perspectives of an industrialist, a state detective and an economist in this matter. The industrialist was a fierce opponent of annexation, while the state detective was convinced that annexionists, those who were in favour of annexation, should mainly be found among major industrialists. The economist, on the other hand, did not rule out the possibility that some of Maastricht’s traders and industrialists would prefer a connection with Belgium. How did they come to these conclusions and to what extent did their considerations and other sources provide an answer to the research question of this article? Taking both gossip and facts into account, we may conclude that indeed there could have been traders and industrialists who supported the Belgian aspirations and preferred to join Belgium. However, the general claim that, in Maastricht especially, major industrialists were in favour of annexation lacks any factual evidence.“
Keywords: Annexion; Erster Weltkrieg; Industrie; Maastricht; Provinz Limburg (Niederlande); Widerstand

Angliederung Eupen/Malmedy an Belgien. Das Schicksal der ehemals preußischen Kreise vor 100 Jahren - Klauser, Klaus-Dieter (Jahrbuch des Kreises Euskirchen, 2022)
Keywords: Annexion; Staatsgrenze

« Les cantons rédimés ». Origines d'une expression controversée. La « désannexion » d'Eupen et de Malmedy à travers le prisme de la presse belge, 1914–1920 - Beck, Philippe (La Belgique et les traités de paix. De Versailles à Sèvres (1919–1920). Actes de colloque, Bruxelles, 09–11 mai 2019, 2021)
Keywords: Annexion; Erster Weltkrieg; Ostbelgien; Presse; Versailler Vertrag (1919)

Die Bedingungsklausel für Eupen-Malmedy im Versailler Vertrag - Jousten, Wilfried (Zwischen Venn und Schneifel, 2021)
Keywords: Annexion; Eupen-Malmedy; Staatsgrenze; Versailler Vertrag (1919)

Overlapping borders. Images of East Belgium as a transcultural area in contemporary East Belgian literature - Beck, Philippe; Penné, Lesley (Oxford German Studies, 2019)
„In this contribution, we discuss how the East Belgian authors Hannes Anderer, Freddy Derwahl and Leo Wintgens represent history, borders and multilingualism in their novels. These contemporary authors have understood that coming to terms with the past is an important aspect in developing a genuine East Belgian collective identity. Furthermore, the multiple borders (with Germany, the Netherlands and Luxembourg) and the co-existence of several languages in this region have become constitutive of collective self-understanding, also with regard to the construction of a region-specific cultural memory. Finally, we show the narrative strategies used in the novels Unterwegs zu Melusine (2006), Bosch in Belgien (2006) and Wege aus Sümpfen. Roman einer Grenzlandschaft Teil I (2001) and Teil II (2006) in order to bring to bear the relation between minority and majority culture by recurring to imagology.“
Keywords: Annexion; Geschichtsbild; Geschichtsschreibung; Kulturelle Identität; Mehrsprachigkeit; Schriftsteller; Staatsgrenze

"New Belgians" living in an ancient Belgian soil? The annexation and integration of the East Cantons - Brüll, Christoph (Beyond the Great War. Belgium 1918–1928, 2018)
Keywords: Annexion; Staatsgrenze; Versailler Vertrag (1919)

La restauration des forêts belges après la Première Guerre mondiale et le rôle décisif de l’administration forestière dans le cadre de l’annexion des cantons d’Eupen-Malmedy - Tallier, Pierre-Alain (Art&Fact, 2018)
Keywords: Annexion; Aufforstung; Forst; Staatsgrenze; Wald

Pierre Nothomb, het comité de politique nationale en de Belgische annexionistische campagne tijdens en na de Eerste Wereldoorlog - Waele, Maria de (Studies over De Sociaaleconomische Geschiedenis Van Limburg/Jaarboek Van Het Sociaal Historisch Centrum Voor Limburg, 2015)
Keywords: Annexion; Erster Weltkrieg; Nothomb; Pierre (1887–1966); Versailler Vertrag (1919)

"Left to Their Own Devices". Belgium's Ambigious Assimilation of Eupen-Malmedy (1919–1940) - O'Connell, Vincent (Revue Belge d’Histoire Contemporaine, 2013)
„The inter-war period in Eupen-Malmedy remains a sensitive arena in which the experiences and sensibilities of its inhabitants have barely been broached by historians. The controversial milestones of the interwar period in Eupen-Malmedy have been covered over with the palimpsest of what the late Tony Judt has referred to elsewhere as ‘selective forgetting’ where communities as well as individuals shield certain episodes or events of the past from intrusion by historians1. The German historian Freddy Cremer describes this phenomenon as akin to ‘amnesia as therapy’. The period following the Nazi invasion and annexation of the former Germany districts in 1940 and their later liberation conspired to further compound an already complex situation. Since then the historical narrative has been shrouded beneath a veil of silence. This article aims in some small way to pull back this veil so that in Cremer’s words “the past may not be left untouched”.“
Keywords: Annexion; Eupen-Malmedy; Staatsgrenze; Versailler Vertrag (1919)

Belgien und die Ostkantone im Versailler Vertrag. Irredenta-Gebiet, militärische Pufferzone oder Trostpreis? - Balace, Francis (Zoom 1920–2010. Nachbarschaften neun Jahrzehnte nach Versailles, 2012)
Inhaltsverzeichnis: http://digitale-objekte.hbz-nrw.de/storage2/2018/03/07/file_36/7584537.pdf
Keywords: Annexion; Eupen; Malmedy; Ostbelgien; Staatsgrenze; Versailler Vertrag (1919)

Last Chance. Belgium at Versailles - Tuyll, Hubert P. van (Boundaries and their meanings in the history of the Netherlands, 2009)
Keywords: Annexion; Erster Weltkrieg; Grenzgebiet; Luxemburg; Ostbelgien; Provinz Limburg (Niederlande); Seeländisch-Flandern; Versailler Vertrag (1919)

Querelles d’Allemands entre Locarnistes. La Question d’Eupen-Malmédy - Poulain, Marc (Revue historique, 1977)
Keywords: Annexion; Eupen-Malmedy; Versailler Vertrag (1919)

Deutsche Annexionspolitik im Westen. Die Wiedereingliederung Eupen-Malmedys im 2. Weltkrieg - Schärer, Martin R. (Lang, 1975)
Keywords: Annexion; Eupen; Malmedy; Ostbelgien; Zweiter Weltkrieg

La Belgique et Eupen-Malmédy. Où en Sommes-Nous? - Werveke, Pierre van (Les Éditions du Pays Belge, 1937)
Keywords: Annexion; Eupen-Malmedy

Eupen et Malmédy dans l’Unité Belge - Werveke, Pierre van (Librairie Albert Dewit, 1922)
Keywords: Annexion; Eupen-Malmedy

La Nationalité des Habitants des Cercles d’Eupen et de Malmédy d’Après le Traité de Paix de Versailles - Nisot, Joseph (Journal du Droit International, 1921)
Keywords: Annexion; Eupen-Malmedy; Staatsangehörigkeitsrecht; Staatsgrenze; Versailler Vertrag (1919)

Une Souveraineté sous Condition Résolutoire. Les Cercles d’Eupen et de Malmédy à la Belgique - Werveke, Pierre van (Revue de Droit International et de Législation Comparée, 1920)
Keywords: Annexion; Eupen-Malmedy; Staatsgrenze; Versailler Vertrag (1919)